Open-label nonrandomized phase IB study to characterize the safety and recommended dose of tinostamustine in combination with nivolumab in patients with advanced melanoma (ENIgMA) - Joerger, Markus; Diem, Stefan; Wyss, Nina; Koster, Kira-Lee; Besse, Lenka; Hess, Dagmar; Metaxas, Yannis; Flynn, Marie-Claire; Aeppli, Stefanie; Abou, Marie Therese; Philip El Saadan, Taemer; Mane, Shrunal; et al. (Melanoma research, 2025)
Tinostamustine is a first-in-class alkylating deacetylase inhibitor that facilitates access to cancer cell DNA, resulting in its damage and counteracting DNA repair systems. We hypothesize that the addition of tinostamustine to immune checkpoint inhibitors (ICIs) improves melanoma treatment. This open-label, nonrandomized phase IB study characterized dose-limiting toxicity (DLT) and the recommended dose (RD) of 2-weekly intravenous tinostamustine at escalating doses of 15 and 30 mg/m 2 when administered with 2-weekly nivolumab 3 mg/kg added in cycle 2 in patients with melanoma. We included 17 patients (four at 15 mg/m 2 and 13 at 30 mg/m 2 tinostamustine). A total of 13/17 (77%) patients were ICI-resistant, 7/17 (41%) had unfavorable melanoma subtypes. No DLT was identified. Tinostamustine RD was 30 mg/m 2 every 2 weeks. One patient experienced grade 2 nivolumab-associated immune-related pneumonitis. Tinostamustine-associated grade 3 leukocytopenia was documented in one patient, grade 2 leukocytopenia in five patients, and grade 1 thrombocytopenia in three patients. Treatment discontinuation occurred in one patient for nivolumab-associated immune-related pneumonitis and in another patient for tumor-related hemorrhage. A total of 7/13 (54%) evaluable patients had at least stable disease as best treatment response, including 3/13 (23%) patients with a confirmed partial response. Median progression-free survival was 8.3 weeks [95% confidence interval (CI): 2.4-15.4 weeks), median overall survival was 19.1 weeks (95% CI: 2.4-41 weeks). Two-weekly intravenous tinostamustine at an immune-modulatory dose of 30 mg/m 2 is safe when coadministered with nivolumab 3 mg/kg and resulted in 54% disease stabilization and 23% confirmed partial responses in patients with predominantly ICI-resistant, advanced melanoma.
Keywords: nádory kůže; nivolumab; Humans; Skin Neoplasms; lidé středního věku; melanom; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; senioři; lidé; Nivolumab; Adult; ženské pohlaví; Male; Middle Aged; Melanoma; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; senioři nad 80 let; mužské pohlaví